INVESTIGATION OF HEAT TREATMENT EFFECTS ON THERMAL AND ELECTRICAL PROPERTIES OF NITIV SHAPE MEMORY ALLOYS - AL-JAF, AHMED OMAR ALI (Fırat Üniveristesi, 2019)
Bu çalışmada, iki farklı oranda Ni48Ti51V1 (V1) – Ni48Ti47V5 (V5) şekil hatırlamalı alaşımlar yüksek saflıkta toz elementler kullanılarak üretildi. Üretim için metal toz karışımları pellet haline getirildi ve pelletler ark eritme fırınında vakum altında üretildi. üretim sonrası her iki alaşımdan parçalar kesilerek, 873K, 973 K, 1073 K ve 1173 K de birer saat ısıl işlem uygulandı. Isıl işlem sonrası alaşımlarda meydana gelen değişimler, Diferansiyel Taramalı Kalorimetre (DSC), x ışınları difraktogramı, Taramalı elektron mikroskobu (SEM) ve sıcaklığa bağlı Fiziksel özellik ölçüm cihazı (PPMS) kullanılarak tespit edildi. DSC ölçümlerine göre, V1alaşımının oda sıcaklığında martensit fazda (B19'), V5 alaşımının ise austenit fazda (B2) olduğu tespit edildi. Isıl işlem ile ara faz olan rombohedral faza (R faz) rastlanmıştır. Benzer fazlar X ışınları- SEM-EDX ölçümleri ile de desteklenmiştir. Sıcaklığa bağlı elektriksel direnç ölçümleri sonrasında austenit fazda alaşımların direnç değerlerinin düşük, martensit fazda yüksek olduğu belirlenmiştir. Ayrıca, ısıl işleme bağlı tane boyutunun artmasıyla bağlantılı olarak, elektriksel direnç değerlerinde benzer değişimler gözlenmiştir.

In this study, Ni48Ti51V1 (V1) - Ni48Ti47V5 (V5) shape memory alloys were produced using high purity powder elements in two different ratios. Metal powder mixtures were pelleted for production and the pellets were produced under vacuum in the arc melting furnace. After the production, pieces of both alloys were cut and one hour heat treatment was applied at 873K, 973 K, 1073 K and 1173 K. Variations in the alloys after heat treatment were determined by using Differential Scanning Calorimetry (DSC), X-ray diffractogram, Scanning electron microscope (SEM) and temperature dependent Physical Property Measurement (PPMS) device. According to the DSC measurements, V1 was determined to be in the martensite phase at room temperature (B19') and the V5 alloy in the austenite phase (B2). The rhombohedral phase (R phase), which is the intermediate phase was encountered by heat treatment. Similar phases are supported by X-rays - SEM-EDX measurements. It was determined that the electrical resistivity values of the alloys were low in the martensite phase and high in the austenite phase after the electrical resistivity measurements. In addition, similar variations in electrical resistivity values have been observed in connection with the increase in grain size due to heat treatment.
NiTiV şekil hatırlamalı alaşımların termal ve elektriksel özellikleri üzerine ısıl işlemin etkilerinin incelenmesi
Keywords: Fizik ve Fizik Mühendisliği